The Determinant of Vitamin D Adequacy in Fishermen - Irawati, Deasy; Ekawanti, Ardiana; Nurbaiti, Lina (Faculty of Medicine Universitas Mataram, 2020)
Background: The prevalence of vitamin D deficiency in both developed and developing countries are 30% - 75% with increased risk reported among women, elderly, obese individuals and those with low sun exposure. Fisherman has been acknowledged as an occupation with high sun exposure. However, a previous study showed that 4 in 5 fishermen were vitamin D deficient. The objective of this study is to investigate vitamin D intake and sun exposure among fishermen. Method: This cross-sectional study recruited fishermen residing in the working area of several public health centres in Mataram and West Lombok districts. The subjects were classified as fishermen and non-fishermen. Vitamin D intake and sun exposure were the the main variables. Results: One in two fishermen and three in four non-fishermen exhibited low intake of vitamin D. Fish intake in the fisherman and the non-fisherman groups were 937 gram per week and 652 gram per week, respectively. The most consumed fish was tuna. Fish intake of 937 gram per week was equivalent to 12 Âµg vitamin D intake and 23.6 nmol/L vitamin D concentration. The majority of subjects were unable to achieve the optimal UVB radiation. Conclusion: Insufficient vitamin D intake and limited sun exposure are prevalent in fisherman and non-fisherman groups.